The role of main five sme industrial estates in sri lankan economic development - Pushpanathan, A.; Ragulan, N. (Shanlax International Journal of Management, 2016)
SME sector in Sri Lanka plays a vital economic role, just as in other developing countries. They are the engine of economic growth and equitable distribution throughout the country. The contribution of rural industries is energetic in such a development. So it is vibrant that the rural industrial development is important by the same token as that of SMEs in Sri Lanka. As a consequence, it is imperative to upgrade the rural economic infrastructure to enable the rural industrialists to provide world class products which can compete locally and internationally. There are remarkable differences between countries and between regions in the developing world. Some regions and countries, notably in East Asia, are rapidly catching up to industrialized countries. Others, especially in Sub-Saharan Africa, are lagging far behind and the share of poor people in the population has even increased in some countries. Industrial development has had an important role in the economic growth of countries like China, the Republic of Korea (Korea), Taiwan Province of China (Taiwan), and Indonesia. Along with accelerated growth, poverty rates have declined in many countries. Some countries have managed to achieve growth with equity, whereas in others inequality has remained high. Among such Asian countries, Sri Lanka is one of the emerging economies which has waged a battle which in bringing in positive results for development. Amongst the many challenges found within the country, economic development is one of the most important one. Present study is to analysis that the Small and Medium Enterprises (SME) play a significant role in achieving economic development. Recognizing the importance of this sector, the Sri Lankan government tends to provide more SME support in their quest to secure a sustainable growth particularly during this turbulent time.
Keywords: SME; Economic development; Significant Role of SME